Is the Prosperity Gospel, Gospel? An Examination of the Prosperity and Productivity Gospels in African Christianity - Barron, Joshua R. (Conspectus : The Journal of the South African Theological Seminary, 2022)
The teaching of the Prosperity Gospel is widespread throughout African Christianity—especially within African Initiated/Independent Churches (AICs) and Pentecostal churches. For many, it is only a natural expression of biblical teachings on abundant life from the viewpoint of Africa’s holistic worldviews. For others, it arises as an extension of the deliverance theology of Pentecostals. Why should God not deliver us not only from sin and sickness, but from poverty as well? Others look at what seem to be the clear abuses of certain well-known (and financially welloff) prosperity teachers and cry, heresy! But are African expressions of the Prosperity Gospel heretical? Or are they orthodox, or perhaps heterodox? Both Scripture and historical Christian tradition reflect an ambivalence toward material wealth, at times seeing it as a blessing and at times as a danger. Reflecting on Scripture in the context of years of pastoral experience in Africa and recent discussions with scholars, missionaries, and local church leaders, this essay is built upon a hybrid methodology of integrative literature review and narrative literature review. After reviewing biblical teachings on wealth and possessions, it reviews the literature on the Prosperity Gospel in Africa and discovers that in some African contexts an adaptation of prosperity teachings, the Productivity Gospel, has arisen to address the same set of questions. Borrowing emphases from Prosperity theology on abundant life and Pentecostal theologies of empowerment, with the accountability of a Weberian work ethic in the context of a holistic African worldview, the Productivity Gospel provides a message of hope and an opportunity for a redemptive (and economic) uplift while avoiding problematic praxis.
free
Keywords: African worldviews; Hope; Prosperity gospel; culture of envy; productivity gospel